Gram-Scale Synthesis and Supramolecular Complex of Precursors of Clar’s Hydrocarbon Triangulene - Ribar, Peter (Org Lett, 2019)
[Image: see text] We present to date the most efficient gram-scale synthesis of triangulene-4,8-dione and 12-hydroxytriangulene-4,8-dione, the precursors of Clar’s hydrocarbon, in overall yields >50%. The direct dihydroprecursors of triangulene, obtained upon reduction of triangulene-4,8-dione, were stabilized in a supramolecular complex with a tetracationic cyclophane ExBox(4+) and characterized by single-crystal X-ray crystallography. This result represents the first step in an endeavor to stabilize the fragile core of triangulene in an inclusion complex in solution and solid state.